(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
Inspired by macroscopic high dimensional graphene materials, graphene fibres now have been fabricated in a range of methods, including drawing, solution spinning, thermal process, electrospinning, etc. Among them, most attractive, large-scale and widely used methodology is solution spinning liquid crystal graphene oxide, including wet spinning and dry-jet wet spinning. Properties of diRerent kinds of graphene fibres were discussed in this review. Both neat graphene fibres and hybrid graphene fibres show remarkable mechanical and electrical properties, actuating properties and flexibility. Multifunctional properties provide graphene fibres potential in functional textiles, flexible and wearable sensors, supercapacitors, electrodes of supercapacitors, energy devices, and actuators etc. It is prospected that properties of graphene fibres will be further optimized, and their application will be more realistic and well developed.